2023
DOI: 10.1093/function/zqad001
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal-Specific KO of the Circadian Clock Protein BMAL1 Alters Blood Pressure Rhythm and Timing of Eating Behavior

Abstract: Brain and muscle ARNT-like 1 (BMAL1) is a core circadian clock protein and transcription factor that regulates many physiological functions, including blood pressure (BP). Male global Bmal1 knockout (KO) mice exhibit ∼10 mmHg reduction in BP, as well as a blunting of BP rhythm. The mechanisms of how BMAL1 regulates BP remains unclear. The adrenal gland synthesizes hormones, including glucocorticoids and mineralocorticoids, that influence BP rhythm. To determine the role of adrenal BMAL1 on BP regulation, adren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…activity and BP rhythm periods that were shortened by 1 hour. 61 Furthermore, the peaks in BP and activity rhythms were delayed by two and 3 hours respectively. 61 These mice also had altered eating behaviour with a reduction in nighttime food intake and an increase in daytime intake.…”
Section: Blood Pressurementioning
confidence: 99%
See 3 more Smart Citations
“…activity and BP rhythm periods that were shortened by 1 hour. 61 Furthermore, the peaks in BP and activity rhythms were delayed by two and 3 hours respectively. 61 These mice also had altered eating behaviour with a reduction in nighttime food intake and an increase in daytime intake.…”
Section: Blood Pressurementioning
confidence: 99%
“…In conditions where ACTH or cortisol production is abnormal, such as Addison's disease or Cushing's Syndrome, the circadian rhythm of BP is disrupted 58–60 . The impact of the adrenal gland on circadian rhythms has been further explored in adrenal specific BMAL1 KO mice 61 . These mice displayed activity and BP rhythm periods that were shortened by 1 hour 61 .…”
Section: Circadian Physiologymentioning
confidence: 99%
See 2 more Smart Citations
“…In a timely investigation, Costello et al generated an adrenal-specific BMAL1 KO mouse to study the influence of the adrenal gland on blood pressure regulation and blood pressure rhythms. 9 Given that female kidney-specific BMAL1 KO mice do not exhibit changes in blood pressure or blood pressure rhythms, Costello et al focused on males. This study found that KO of BMAL1 in the zona glomerulosa of the adrenal cortex resulted in a shortened blood pressure and activity period, and a delayed peak of both blood pressure and activity.…”
mentioning
confidence: 99%